The Lymphotoxin-β Receptor Is Necessary and Sufficient for LIGHT-mediated Apoptosis of Tumor Cells - Rooney, Isabelle A.; Butrovich, Kris D.; Glass, Alison A.; Borboroglu, Stephen; Benedict, Chris A.; Whitbeck, J.Charles; Cohen, Gary H.; Eisenberg, Roselyn J.; Ware, Carl F. (The Journal of biological chemistry, 2000)
LIGHT is a tumor necrosis factor (TNF) ligand superfamily member, which binds two known cellular receptors, lymphotoxin-β receptor (LTβR) and the herpesvirus entry mediator (HveA). LIGHT is a homotrimer that activates proapoptotic and integrin-inducing pathways. Receptor binding residues via LIGHT were identified by introducing point mutations in the A′ → A“ and D → E loops of LIGHT, which altered binding to LTβR and HveA. One mutant of LIGHT exhibits selective binding to HveA and is inactive triggering cell death in HT29.14s cells or induction of ICAM-1 in fibroblasts. Studies with HveA- or LTβR-specific antibodies further indicated that HveA does not contribute, either cooperatively or by direct signaling, to the death pathway activated by LIGHT. LTβR, not HveA, recruits TNF receptor-associated factor-3 (TRAF3), and LIGHT-induced death is blocked by a dominant negative TRAF3 mutant. Together, these results indicate that TRAF3 recruitment propagates death signals initiated by LIGHT-LTβR interaction and implicates a distinct biological role for LIGHT-HveA system.